Assessing Thermal Comfort of Broiler Chicks - Purswell, J.L.; Lott, B.D.; Dozier, W.A.; Roush, W.B.; Branton, S.L. (International Journal of Poultry Science, 2008)
Proper management of the thermal environment during brooding is essential to performance in broilers. Brooding programs used in the broiler industry are prescriptive, but little information exists about thermal comfort in chicks. Identifying thermal conditions that chicks prefer would allow for better management of the thermal environment during brooding. The objective of this study was to determine thermal conditions that are preferred by broiler chicks. Thirty broiler chicks at seven days of age were fitted with a harness holding a miniature temperature data logger; air temperature directly above the chicks` backs was measured every 3 minutes for 7 days from 8 to 14 days of age. Air temperature in the room was measured in 25 locations on the same interval as the harnesses. The room was held at 32.2oC for the first week and reduced to 29.4oC the second week. Air temperature, as measured by the bird harnesses, was significantly higher than measured in the room. Overall least squares means for harness and room temperatures were 33.0 and 29.2oC, respectively and were significantly different (P < 0.0001). The estimated difference between harness and room temperature was 3.8oC with a standard error of 0.06oC; the least significant difference was calculated as 0.15oC.